SMART IRRIGATION SYSTEM USING RASPBERRY PI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In India most of people is doing work related agriculture directly or indirectly. An economy of India is mostly affected by agriculture related activities. To check water level of well, farmer have to go to farm and start water pump. Sometimes he has to go in night. If fire is spread in farm how farmer can know? If he know about it, he cannot do anything about it because many plants burned .In this project, we will make one smart irrigation system which will notify farmer on his registered mobile device and email address, if the soil is dry and it need watering, using soil moisture sensor and also notify by glowing bulb and start motor which is attached with main controller. System is also measuring the water level of well and notify the farmer two times a day. For fire detection we used flame detection sensor and if fire is there in farm system will notify the farmer and also buzzer will blow. The aim of this project is to develop a smart irrigation monitoring system using raspberry pi. Focus area will be parameters such as temperature and soil moisture. This system will be a substitute to traditional farming method. We will develop such a system that will help a farmer to know his field status in his home or he may be residing in any part of the world. It proposes an automatic irrigation system for the agricultural lands. Currently the automation is one of the important role in the human life. It not only provide comfort but also reduce energy, efficiency and time saving. Now the industries use automation and control machine which is high in cost and not suitable for using in a farm field. So here it also to design a smart irrigation technology in low cost which is usable by Indian farmers.Raspberry pi is the main heart of the whole system. An automated irrigation system was developed to optimize water use for agricultural crops. Automation allows us to control appliances automatically. The objectives of this project were to control the water motor automatically, monitor the plant growth using webcam and we can also watch live streaming of farm on android mobiles by using wifi.